Metal-Supported Solid Oxide Electrolysis Cell Test Standard Operating Procedure - Shen, Fengyu; Welander, Martha M.; Tucker, Michael C. (Frontiers in Energy Research, 2022)
This procedure describes the setup and testing protocol for metal-supported solid oxide electrolysis cell (MS-SOEC) button cell performance evaluation. It defines a standard testing protocol, describes materials selection, and identifies common pitfalls for testing MS-SOEC button cells.